Teaching difficulties and personal variables: a study with students of the Master’s Degree in Teaching in Valencia and Sevilla - Sanz-Ponce, J. Roberto; Giménez-Beut, Juan Antonio; García-Grau, Pau; Montoro-Fernández, Elisabeth (Frontiers in Education, 2025)
Teachers are a key element in teaching and require adequate training. To update it, it is proposed to analyse the difficulties that students foresee they will have in their professional future. These represent the training deficiencies of the Master’s Degree in Teaching. The objective is to analyse the main concerns of the Master’s Degree students regarding possible difficulties for their future teaching, taking as a reference the sociodemographic variables: sex and age, as well as the university of origin and geographical location. To carry out this analysis, the difficulties were grouped into academic, organizational, social and material-technological, and were measured by passing a questionnaire. The questionnaire used was the Teaching Problems Inventory. The sample consisted of 992 students from six specialties, from different universities of origin in the Valencian Community and Andalusia. The effect of age and sex on difficulties and the predictive role of these variables on Material and Organizational Difficulties, mediated by Academic and Social Difficulties, were also analysed. A greater concern for material and organizational aspects is evident. Fear of rejection of their potential pedagogical innovations stood out. Concerns about teaching increased with age. Males show greater concerns in Academic and Organizational Difficulties and females in Material ones. Although the sample is high, it would be positive to compare the results with other universities with large student populations.